ABM : fundamentals of accountancy, business and management : a textbook in basic accounting 2 - Frias, Solita A. (Quezon City : Phoenix Publishing House, Inc., 2016)
"Fundamentals of Accountancy, Business and Management : A Textbook in Basic Accounting 2 is the second textbook for the Accountancy, Business, and Management (ABM) Strand. Having completed the study of bookkeeping in the first accounting subject, it is expected that the students will move smoothly to the next level of accounting. Having learned the basic concepts and processes in accounting, the students are now expected to do more than bookkeeping. They will now study (1) the preparation of financial statement and (2) analysis of financial statements for decision-making. Decision-making involves critical evaluation and analysis of information. The activities and exercises at the end of each chapter are designed to enhance the ability for critical evaluation".
Includes references.
English text.
Keywords: Business; Accounting; Management